Silage- and forage-based diets compared to commercial diets in Ugandan pig growth - Carter, N.; Dewey, Catherine E.; Grace, Delia; Lange, K. de (International Livestock Research Institute, 2016)
Introduction: Smallholder pig farmers in east Africa report that lack of feed, seasonal feed shortages, quality and cost of feed are key constraints to pig rearing. Commercially prepared pig diets are too expensive and there is competition for food between pigs and people. Smallholder farmers typically feed nutritionally unbalanced diets. This results in low average daily gain (ADG) and poor farmer profits. The objective was to compare the ADG of Ugandan pigs fed forage- or silage-based or commercial diets. Materials and Methods: Local and crossbred Ugandan weaner-grower pigs were randomly assigned to commercial or forage- or silage-based diets. The forage-based diet, on an as-fed basis included specific amounts (%) of the following ingredients; avocado (25.5 kg), banana leaf (1.7), cottonseed meal (1.8), jackfruit (21.9), maize bran (9.5), sun-dried fish (3.1), sweet potato vine (36.1), limestone (0.14), salt (0.14) and vitamin/mineral premix (0.07). Silage-based diet included similar amounts of cottonseed meal, jackfruit, minerals and vitamins, but more maize bran (12.4), sun-dried fish (2.7), and ensiled sweet potato vine and tubers (60.8). Pigs were individually weighed every 3 weeks from 9 to 32 weeks of age. Pen-level ADG was compared across diets controlling for breed and starting weight using multiple linear regression. Results: ADG of pigs fed commercial diet was higher than those fed forage- or silage-based diets between 9 and 24 weeks of age (p<0.03). Between 28 and 32 weeks, pigs fed forage-based diets had a lower ADG than those on other diets (P<0.001). Least squares mean ADG (g/pig/day) for pigs fed commercial, forage- and silage-based diets were 294, 36 and 52, respectively at 9–15 weeks; 329, 163, 212 at 15–19 weeks; 574, 112, 362 at 20-24 weeks and 1233, 694, and 994 at 28 to 32 weeks of age. Conclusion: Forage-and silage-based diets were unsuitable for newly-weaned pigs, which may be attributed to higher than anticipated diet ash and fiber contents. However, pigs on forage- and silage-based diets grew better than those on smallholder farms once they reached 20–24 weeks and 15–19 weeks, respectively. This was when pigs were approximately 12 kg body weight. Well-balanced cost-effective diets are needed to improve pig performance in east Africa. Fresh and ensiled locally available feedstuffs can be used in diets that meet the nutrient requirements of pigs. Low-cost forage- and silage-based diets containing some zero-cost feedstuffs are needed to improve the potential for profitability of smallholder pig farming. Efficient use of these feedstuffs is required to promote sustainable smallholder pig rearing enterprises.